FACTORS INFLUENCING THE ENGAGEMENT OF MILLENNIAL EMPLOYEES IN SURABAYA-INDONESIA - Bella Vania; Winda Christanto; Juliana Caesaria Tandung; Ruth Srininta Tarigan (International Journal of Financial and Investment Studies (IJFIS), 2022)
Engaged employees tend to produce better results, which no doubt will bring benefits to organizations. Unfortunately, in Indonesia, only 25% of Millennial employees are engaged, while Millennial employees have occupied 35% of the total workforce. This research aims to identify the influence of the seven determinants of employee engagement, namely work environment, leadership, co-worker relationship, training and career development, compensation, organizational policies, and workplace well-being, on the engagement level of Millenial employees in one of the fastest growing industry in Indonesia, which is the Cafe and Restaurant Industry. The initial 115 data have been gathered, and multiple regression analysis shows that the seven determinants explained 93.6% of the variance in employee engagement (Adjusted R2=0.936, F=239.174, p<.000). Furthermore, only five factors show a significant individual influence on the engagement level: leadership (b=328, p<.000), co-worker relationship (b=.239, p<.004), training and career development (b=254, p<.011), compensation (b=383, p<.001), and workplace well-being (b=176, p<.005). Implications for these findings are discussed in the full paper.